Internationale Humanitäre Hilfsorganisation v. Germany. Judgment - Eleni Polymenopoulou (22827065) (2025)
On October 10, 2023, the European Court of Human Rights (ECtHR) issued a judgment upholding the decision of the German authorities to suspend the organization International Humanitarian Aid Association (Hilfsorganisation) because of “knowingly support[ing] international terrorism, directly or indirectly” (para. 102). Germany had shut down Hilfsorganisation, proscribing it and ordering confiscation of its assets, on the grounds that one of the entities it funded was the Gaza-based “Islamic Society” (Salam), which was allegedly affiliated with Hamas (para. 9). According to Germany, this presumed indirect funding of Hamas violated the principle of “international understanding between peoples” (Völkerverständigung) (para. 1), which is entrenched in the German Constitution, and also reflected in the German Associations Act. According to the Federal Constitutional Court, an association “meets the requirements for a prohibition … when it actively advocates and promotes violence or similarly serious actions violating international law, such as terrorism in international relations or among parts of the population,” and this may also be the case “when an association supports third parties. Other Information Published in: American Journal of International Law License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/ajil.2025.10083